Determinação do segundo aminoácido limitante para codornas japonesas - Cavalcante, Danilo Teixeira (2013)
This study aimed to determine the second limiting amino acid for Japanese quails fed with corn and soybean meal. Were used 1296 Japanese quail, females, divided into three experiments. The first experiment was conducted with birds aged 1-21 days, the second experiment with birds of 22-42 days and the experiment III with birds laying phase. The treatments in the three experiments consisted of reduction of crude protein in seven percentage points, approximately, with supplementation of the DL-methionine plus an L-amino acid essential: T1 (Met), T2 (T1+Lys), T3 (T1+Thr) and T4 (T1+Trp), T5 (T1+Val), T6 (T1+Arg), T7 (T1+Ile) and T8 (All). The parameters evaluated were feed intake (g/bird), weight gain (g/bird), feed conversion (g/g), laying rate (%), average egg weight (g), egg mass (g ), feed conversion per egg mass (kg feed/kg egg), feed conversion per dozen eggs (kg feed/dozen eggs), average weight of constituents (yolk, albumen and shell) eggs (g) , bark thickness (mm) and specific gravity (g/cm³). The statistical design was a completely randomized and the test for comparison of means was SNK at 5% probability. For performance results of 1-21 and 22-42 days, the weight gain and feed conversion were affected by amino acid supplementation. In the laying phase, feed intake, egg production, egg mass, and mass conversion per dozen, yolk weight and albumen weight were affected. We conclude that the second limiting amino acid for Japanese quails in phases 1-21 and 22-42 days, is lysine. During the laying period, it was not possible to determine the second limiting amino acid, meeting the requirements of methionine + cystine, lysine, threonine, tryptophan, valine, arginine and isoleucine digestible to obtain better results is required.